2012
DOI: 10.1186/2193-0414-1-2
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of factors affecting fire performance of mattresses: a review

Abstract: An in-depth analysis of U.S. residential fire statistics shows that although the total number of fires and deaths due to mattress fires has dropped as a result of several regulatory approaches, the mattress/bedding fires continue to account for one of the largest shares of residential fire deaths and injuries. To address the increasing number of deaths per 1000 mattress/bedding fires, the open flame mattress flammability regulation (16 CFR 1633) was introduced in 2007. The 16 CFR 1633 prescribes performance st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 14 publications
1
12
0
Order By: Relevance
“…CA TB 121 ) or dormitories (CA TB 129 ). A review of the development of mattress fire tests can be found in .…”
Section: Introductionmentioning
confidence: 99%
“…CA TB 121 ) or dormitories (CA TB 129 ). A review of the development of mattress fire tests can be found in .…”
Section: Introductionmentioning
confidence: 99%
“…However, this trend 41 must change in the next few years in order to achieve the targets proposed by the European 42 Parliament for landfilling (European Commission, 2014). These facts, together with the high 43 recoverable energy value of this type of waste, comparable to coal and slightly less than that of 44 fuel oil, make the waste-to-energy the best disposal option (Guo et al, 2014;Nazaré et al, 2012). 45 VMF was developed in 1966 by NASA's Ames Research Center (Simón et al, 2015), but it 46 did not arrive in the public domain until 1991 when the first viscoelastic mattress was marketed.…”
Section: Viscoelastic Memory Foam (Vmf) Is a Polyurethane-based Foam mentioning
confidence: 99%
“…A more detailed report on assessment of factors affecting fi re performance of mattresses is available elsewhere. 43 …”
Section: (D)mentioning
confidence: 97%